Study of the Seawater Desalination Performance by Electrodialysis - Jihong Shi; Liang Gong; Tao Zhang; Shuyu Sun (Membranes, 2022)
The global scarcity of freshwater resources has greatly contributed to the development of desalination technologies, in which electrodialysis desalination is one of the most widely used and highly regarded methods. In this work, the first step was to design and assemble a experiment module for electrodialysis desalination. The ion removal efficiency and single membrane mass transfer flux of electrodialysis desalination were investigated. The results show that the desalination performance of the module is improved by increasing the voltage gradient, increasing the concentration of seawater and electrolyte and decreasing the membrane surface flux and that the optimum operating conditions for the module at 24 V operating voltage are feedstock concentration of 35 g/L, electrolyte concentration of 1.42 g/L which and system flow rate of 15 L/h. The results of the study will help to better investigate electrodialysis desalination technology.